EFFECT OF MADHUGHRITA YAPANAVASTHI IN TREATMENT OF LUMBAR SPONDYLOSIS - Kumar K S, *Praveen; T K, Sujan (International Journal of Ayurveda and Pharma Research, 2017)
Lumbar spondylosis, a degenerative condition of lumbar spine is affecting majority of adults presently. The treatment options available nowadays are diverse and often undependable ensuing rising costs and variability in management throughout the country. It may be considered as Kateegraha owing to the grasping pain or stiffness in the Katee Pradesha. Katee is one of the Vatasthaanas and pain/stiffness is caused by Vata, hence Kateegraha may be considered as Vatavyadhi. Vasthi therapy is the Agryachikitsa for Vata Dosha which can be done here. Madhughrita Yapanavasthi is Vatahara, Brumhana and Trikaprishta Soolahara. It would be especially good in degenerative conditions associated with pain affecting Trika region like Lumbar spondylosis. The study design was of interventional type. Twenty patients, satisfying the selection criteria were selected from the OPD of Govt. Ayurveda College Panchakarma Hospital, Thiruvananthapuram. They were given Deepana Pachana first, and then Snehasweda and finally Madhughrita Yapanavasthi for 8 days while the follow up period were for 16 days. The assessment was done before treatment, after treatment and after follow up. Changes in the following variables- pain, stiffness, tenderness, range of movements and muscle strength were analyzed. For all variables except the muscle strength p value were statistically significant at the level of 0.001. The p value for Muscle strength was significant at the level of 0.05 for after treatment - after follow up comparison. And it was significant at the level of 0.01 for before treatment - after follow up comparison. Madhughrita Yapanavasthi is thus effective in managing Lumbar spondylosis.